Insights into the mechanical and environmental behaviours of artificially phosphogypsum-based lightweight aggregate and its sustainable application - Jun Wu; Yahui Li; Yunzhi Tan; Youlun Chen; Chong Wang; Lun Zhang (European Journal of Environmental and Civil Engineering, 2026)

Sulfate-catalyzed denitrifying anaerobic methane oxidation process mediated by Methanobacterium sp. from digestion sludges - Shibo Fu; Wen-Bo Nie; Xin Tan; Xiaoming Wang; Lili Li; Guo-Jun Xie (Water Research, 2026)

A process of microwave pyrolysis treatment of amidoxime functionalized fiber and enrichment of uranium for uranium extraction from seawater - Shen Zhang; Wencai Cheng; Junwen Tan; Benyao Yu; Tianjun Li; Congcong Ding; Xirui Lu; Jun Wen; Hao Li (Desalination, 2026)

Epigenetic silencing of DLEC1 correlates with tumor immune microenvironment and predicts immunotherapy prognosis in multiple cancers - Ruijie Ming; Qi Xiong; Shuh-Ying Tan; Lili Li; Shujie Bao; Jianhua Wang; Lijuan Zhao; Xiaoqian He; Zeze Zheng; Yan Wang; Xiaoyu Liu; Jun Tang; et al. (Human Genetics, 2026)
Cancer remains a major health issue globally, with increasing incidence and mortality rates. While immunotherapy has revolutionized cancer treatment, not all patients benefit, urging the identification of predictive biomarkers. This study utilized public datasets and tumor samples to examine the expression and promoter hypermethylation of DLEC1 in normal and tumor tissues, to evaluate its potential as prognostic and immunotherapy marker. In vitro and in vivo experiments on breast cancer (BrCa) cell lines were conducted to explore the functions and mechanisms of DLEC1 . The prognostic significance of DLEC1 downregulation and its impact on immune cell infiltration and immunotherapy efficacy were analyzed using the GEO and TCGA databases. DLEC1 was frequently downregulated and methylated across multiple cancers. In BrCa, expression of DLEC1 inhibited tumor cell proliferation, induced apoptosis, and activated the interferon lambda1 signaling pathway, indicating its important role as a bona fide tumor suppressor and immunoregulator. High DLEC1 expression correlated with better prognosis in several cancer types and with increased immune cell infiltration. Cancer patients with high DLEC1 expression showed improved overall and progression-free survival under immune checkpoint inhibitor therapies, such as anti-CTLA4, anti-PD1 and anti-PDL1. DLEC1 promoter hypermethylation is a promising biomarker for cancer prognosis and potential immunotherapy response prediction. Its expression and promoter hypermethylation status could thus help to guide clinical treatment strategies for cancer patients, particularly of breast cancer.

A dynamic prediction method for maize ear yield by fusing morphological and kinetic features - Li Tan; Qiankun Fu; Fan Zhang; Jun Fu; Fengxin Yan; Naimov Alisher (Biosystems Engineering, 2026)

Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

Dual-stage evolution mechanism of full-scale pore structure in lignite during low-temperature oxidation - Tianze Li; Bo Tan; Liyang Gao; Yunfei Zuo; Longkun Sui; Xinyu Xiang; Jun Zhou; Haiyan Wang (Fuel, 2026)

Benzimidazole functionalization enables efficient multi-resonance TADF with accelerated spin-flipping and balanced charge transport - Ji-Hua Tan; Si-Wei Chen; Xin-Lu Li; Han-Nan Shi; Xiao-Long Liu; Yao-Zu Su; Xiaofeng Wang; Jun-Hua Zhuang; Chengxiang Shi; Jia-Ming Jin; Shaoyun Yin; Jia-Xiong Chen; et al. (Chemical Engineering Journal, 2026)

Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

DAMPs and PAMPs driven macrophage activation in kidney injury - Jia-hui Li; Zhu-jun Wu; Wan-ting Li; Chun-yin Lv; Li Wang; Rui-zhi Tan (Tissue and Cell, 2026)

PpPRE1 and PpPRE2 mediate gibberellin-induced internode elongation by regulating brassinosteroid biosynthesis in peach - Huanbing Lu; Mengmeng Zhang; Ning Liu; Bo Zhao; Jun Cheng; Bin Tan; Xianbo Zheng; Wei Wang; Xia Ye; Haipeng Zhang; Xiaobei Wang; Zhiqian Li; et al. (Plant Science, 2026)

Soil function assessment in smelting sites: Conceptual evolution, methodological advances, and future directions for sustainable land remediation - Shengguo Xue; Xingyao Tan; Haixia Liang; Wenyan Gao; Yayuan Huang; Feng Zhu; Jun Jiang; Chuan Wu; Xue Li (Journal of Environmental Sciences, 2026)

A synergistic antifungal buccal composite integrating Aureobasidin A and alkaline modulation for localized treatment of oral candidiasis - Jiaxin Yi; Li Xie; Xueping Shui; Xinzhi Tan; Yandong Mu; Wei Fei; Li Xiao; Weidong Tian; Jun Guo (Chemical Engineering Journal, 2026)

Multi-stimuli responsive cellulose nanocrystal-based microcapsules with enhanced insecticidal efficacy and environmental safety - Er-min Zhou; Jia-wei Ding; Dao-bing Kang; Yi-lin Tan; Yong-jiang Li; De-qiang Li; Jun Li (Carbohydrate Polymers, 2026)

From lignin-carbohydrate complex cleavage to mesoporous cellulose: A multi-scale study on diethylene glycol-ferric chloride pretreatment of timothy straw - Song Tang; Fei Zhou; Bokun Zhou; Jun Li; Jiale Zhang; Junting Li; Jing Zhang; Xin Tan; Yequan Sheng (Biomass and Bioenergy, 2026)

Co-P-O bridges enabling spin-related interfacial charge regulation for synchronizing redox kinetics in dual-pollutant purification - Haili Zhao; Jiaxin Tong; Pengfei Tan; Huanhuan Zhai; Haiyan Wu; Tingting Li; Chuangxin Cai; Bowen Qi; Jun Pan (Water Research, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

The narrow-spectrum circadian rhythm promotes the photosynthesis and pigment accumulation of celery within two days (light/dark: 12 h/12 h) - Chen Chen; Li-Xiang Wang; Meng-Yao Li; Guo-Fei Tan; Ting Huang; Jing Zhuang; Jin-Song Xiong; Jun Yan; Ai-Sheng Xiong (Journal of Photochemistry and Photobiology B: Biology, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Land use legacies shape wild boar (Sus scrofa) diet along a forest-urban gradient in Singapore - Jasmine J. M. Ong; Max D. Y. Khoo; Li Si Tay; Bryan T. M. Lim; Charles J. Marsh; Melvyn Aik San Tan; Wen Xuan Chiok; G. Kenny Png; Matti A. Niissalo; Gillian S. W. Khew; Marcus A. H. Chua; Malcolm C. K. Soh; et al. (Urban Ecosystems, 2026)

Asymmetric Co-O-La coordination achieves biocompatible and selective generation of high-valent cobalt-oxo species for boosting water purification - Qin-Chen Li; Hai-Yan Zhu; Yi-Jun Zhang; Biao Chen; Yong-Sheng Tan; Ya-Meng Dong; Qi-Nian Wang; Wei-Kang Wang; Dong-Hua Xie; Xing Zhang (Journal of Hazardous Materials, 2026)

PpZAT10 inhibits PpTST1 expression to regulate sugar accumulation in peach (Prunus persica) fruit - Qinqi Liu; Beibei Feng; Liuqing Han; Dongsheng Wang; Kexin Liu; Xiaobei Wang; Nan Hou; Lei Wang; Xianbo Zheng; Xiaodong Lian; Jun Cheng; Wei Wang; et al. (Plant Science, 2026)

Chemical-free lithium separation from high-salinity brines using model-informed and machine learning-optimized multi-column zwitterionic chromatography - Jun Woo Park; Daniel Li; Marcus Condarcure; Zbyslaw Owczarczyk; Ariel R. Lepard; Louis A. Chirban; Joel Miscall; Eric C.D. Tan; Ju Weon Lee; Ki Bong Lee; Hoon Choi (Journal of Cleaner Production, 2026)

Species-specific nutrient acquisition strategies in subtropical afforestation tree species under nitrogen fertilization - Sihui Qiu; Ying-Ping Wang; Shiting Xia; Songjia Chen; Jie Li; Zhongbing Chang; Mengxiao Yu; Yinping Tan; Ziqi Liang; Junhua Yan; Jun Jiang (Plant and Soil, 2026)

PpBRC1 negatively regulates branching via modulating GA signal transduction gene PpGID1b in peach (Prunus persica) - Yulu Wu; Yajia Zhang; Junjie Zhang; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Nan Hou; Xianbo Zheng; Jun Cheng; Wei Wang; Langlang Zhang; Xia Ye; et al. (Plant Cell Reports, 2026)

Effects of continuous light and skeleton photoperiods on photosynthesis and circadian rhythm in celery - Chen Chen; Ting Huang; Li-Xiang Wang; Meng-Yao Li; Guo-Fei Tan; Jing Zhuang; Jin-Song Xiong; Jun Yan; Ai-Sheng Xiong (Biotechnology Letters, 2026)

Targeting complement and coagulation cascades with Buyang Huanwu Decoction attenuates acute inflammation and enhances neuroprotection in spinal cord injury - Dezun Ma; Xinyu Xie; Yijun Ma; Hui Yan; Haoyuan Yin; Xue Tan; Yan Li; Xinpei Lin; Yuexin Huang; Xiang Wu; Zhihao Zhou; Chenglin Yang; et al. (Science China Life Sciences, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Sex-specific responses of intestinal health, microbiota composition, and transcriptome profiles in golden pompano (Trachinotus blochii) subjected to hypoxia and reoxygenation - Xiao Kun Wang; Shan Ying Han; Ze Xin Zhong; Zeng Tan Hu; Tian Xiu Li; Yue Gu; Chun Xiu Jin; Tian Jiang; Fei Biao Song; Jian Luo; Jun Long Sun (Frontiers in Marine Science, 2026)
Introduction Driven by global climate change and coastal eutrophication, severe hypoxic events have become a primary environmental stressor in marine ecosystems, posing a critical threat to commercially vital teleosts like the golden pompano ( Trachinotus blochii ). Understanding the dimorphic physiological and microbial responses between sexes under such stress is crucial for developing targeted mitigation strategies. Methods Golden pompano were subjected to hypoxia stress (3.0 ± 0.2 mg/L) for 14 days, followed by restoration of dissolved oxygen to normoxic state (7.0 ± 0.2 mg/L) and cultivation for another 14 days. Subsequently, the histology ( n = 3), digestive enzyme activity ( n = 9), microbial composition ( n = 3), and transcriptome ( n = 3) of intestinal tissue were evaluated. Results Hypoxia induces marked physiological stress and a shift toward intestinal dysbiosis across both genders, manifested by damaged intestinal integrity, oxidative stress, and an increased abundance of opportunistic pathogens (e.g., Spirochaetes ). Although reoxygenation further deteriorates the histological condition of female intestinal tissue, it also triggers more significant molecular and enzyme activity rebound effects compared to males. Moreover, females exhibit significant upregulation of lipid metabolism, antioxidant defense mechanisms, and key signaling pathways, suggesting that they may have adopted a high-energy “compensatory recovery” strategy. Correlation analyses reveal that these microbial shifts are closely linked to host metabolic regulation: beneficial bacteria ( Pseudoalteromonas and Lactococcus ) support sterol transport and signaling homeostasis, while opportunistic taxa ( Brevinema ) negatively impact lipid synthesis. Discussion Our findings reveal a distinct gender dimorphism in the hypoxia and reoxygenation response, providing a theoretical foundation for sex-specific management and nutritional interventions in golden pompano aquaculture.

Mechanism of GCN2/eIF2α signaling pathway in MC-LR-induced hepatocyte oxidative damage and alpha-lipoic acid intervention - Ailin Tan; Yu Huang; Hanyun Shen; Chaoyun Chen; Qingbi Zhang; Jun Bai; Liangping Luo; Xuelian Jiang; Shuai Li; Zhixia Han (Toxicon, 2026)

Tumor-associated bacterial effectors: novel frontiers in tumor biology and immunity - Jia-Hao Dai; Ying-Qi Lu; Sen-Yu Feng; Xi-Rong Tan; Li-Li Li; Yue-Can Zeng; Jian-Zhou Chen; Jun Ma; Na Liu (Science Bulletin, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

A two-wave panel biomonitoring study of changes in urinary pesticide metabolites and their associations with liver function and inflammatory markers - Dandan Liu; Xiaotong Li; Yuling Chen; Fenfang Deng; Jia He; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Research, 2026)

Polycyclic aromatic hydrocarbon exposure and mitochondrial DNA copy number: Opposing roles of oxidative stress and inflammation - Si Zhou; Wenzhe Su; Lingli Zeng; Jia He; Jun Yuan; Rongfei Peng; Juntao Li; Lei Tan (Environmental Pollution, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Magnetite in lunar impact glasses formed in the presence of water - Ting Li; Jieqi Xing; Yang Li; John A. Tarduno; Xuelin Zhu; Zelong Shi; Ye Zheng; Qian He; Ziying Li; Sheng He; Jun Zhong; Liumin Deng; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Intestinal Mysm1 alleviates colitis-associated depression through the serotonin-dependent gut-brain axis - Qiaozhen Qin; Huaqiang Ruan; Zhenhua Xu; Yuanshuai Li; Wenhao Wu; Xiaotong Li; Jinyu Shi; Heyang Zhang; Yue Chen; Jinwei Liu; Yuanrong Qiu; Yifei Tan; et al. (Science Bulletin, 2026)

Multiscale thermal response and hazardous hydrocarbon gas evolution during low-temperature coal oxidation in sealed fire zones - Bo Tan; Hao Lu; Zhenrong Li; Saiyi Gao; Jinliang Li; Xiyang Fang; Jun Zhou (Journal of Cleaner Production, 2026)

Research on the molecular structure reconstruction and energy evolution mechanism of low-rank coal during low temperature oxidation - Tianze Li; Bo Tan; Jiaxue Yu; Longkun Sui; Yunfei Zuo; Jun Zhou; Haiyan Wang (Journal of Environmental Chemical Engineering, 2026)

Polystyrene microplastics impaired decidualization in mice via oxidative stress and inflammation and disrupted the reproductive function of their female offspring - Weike Li; Boyin Tan; Jun Xiong; Jiani Diao; Jing Wang; Jing Long; Zhenyin Chen; Yuguang He; Xuemei Chen; Fei Han; Fangfang Li; Junlin He; et al. (Journal of Environmental Sciences, 2026)

H2-induced restructuring of Mn for highly dispersed Pt species on PtMn/S-1 toward enhanced propane dehydrogenation - Jiamin Liu; Caixin Zou; Lizhi Wu; Jun Zuo; Mengjia Zhu; Qiwei Duan; Zhuangzhuang Ren; Juncheng He; Yirong Wang; Yu Tang; Zhuoxi Zhuo; Li Tan (Chemical Engineering Journal, 2026)

Charge interaction and local structure induced abundant sulfur vacancies and lattice strain in NiS/NiS₂ heterojunction for efficient overall water splitting - Meng Jin; Yuqing Liu; Longyu Qiu; Xuanlin Kuang; Xiaoping Hu; Jun Zhang; Yin Liu; Juan Liu; Chuan Tan; Menggang Li; Shi-Yu Lu (Chemical Engineering Journal, 2026)

MnO2/CNT-Modified Anode Microbial Fuel Cells for Removing Varying Amounts of Cu2+ from Wastewater - Jiahui Zhu; Lingling Li; Jun Zhou; Nasha Dou; Lei Gong; Mingjing Li; Hui Tan; Ping Yang; Wenfeng Wang (Water, Air, & Soil Pollution, 2026)

Seismic Noise Attenuation in Imaging Gathers Using a Residual U-Net: Application to Seismic Data from the Xihu Sag - Dewen Qin; Jian Li; Yong Jiang; Wensun Yin; Xiuping Jiang; Jun Tan; Qingquan Li; Jianlei Zhang; Yanjiao Wang (Journal of Ocean University of China, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Cu-catalyzed deaminative thiocyanation of anilines via nitrate reduction - Yong-Sheng Zhou; Yan Yang; Jing-Yao Zhou; Li-Jun Xu; Yi-Xie Tan; Xin-Chun Zhang; Liang Wang (Molecular Diversity, 2026)

Colaconema zhanjiangensis sp. nov. (Colaconemataceae, Rhodophyta): a new epi-endophytic filamentous red algal species from China - Haiping He; Nenghui Li; Hongyan Cai; Jun Zeng; Hang Li; Huihui Wang; Huaqiang Tan; Enyi Xie (Algae, 2026)
The genus Colaconema represents a significant group of filamentous red algae that commonly grow as epiphytes, endophytes, or epi-endophytes on a variety of economically important macroalgae, potentially affecting host health and aquaculture productivity. Although numerous Colaconema species have been described worldwide, few have been reported from China based on integrated morphological and molecular analyses. In this study, Colaconema specimens were collected from the red macroalgae Solieria sp. in Zhanjiang City, Guangdong Province, China, and identified through detailed morphological observations combined with rbcL and 5′ region of cytochrome c oxidase subunit I (COI-5P) sequence analyses. Morphological examination revealed cylindrical cells (23–26 × 6–8 μm), irregularly branched filaments, a single plastid with a single pyrenoid, and ovoid monosporangia (11–12 × 7–9 μm) arranged in various patterns. Molecular analyses demonstrated sufficient sequence divergence from other Colaconema species (rbcL: 5.06–13.65%; COI-5P: 7.23–13.09%), supporting the recognition of these specimens as a new species. The findings expand the current understanding of species diversity within the genus.

Downregulation of intracellular ATP levels by PANX1 inhibits ovarian granulosa cell proliferation and mediates follicular dysplasia in elderly women - Zhiqin Zhang; Xuechen Sun; Xin Li; Peipei Liu; Liyun Cao; Shenggen Long; Jun Tan (Reproductive Biology, 2026)

Resveratrol blocks the spoilage and virulence phenotypes of Aeromonas salmonicida isolated from sturgeon by inhibiting quorum sensing - Mingxia Tu; Yu Rao; Lei Liu; Chunming Tan; Liang Gao; Jun Li; Xia Gao; Meng Gui (Food Research International, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Design of highly efficient and carbon-resistant catalysts for biogas reforming using entropy engineering strategy - Bing Han; Zetao Huang; Zuhao Li; Zhige Zhang; Tao Tan; Jun Xie; Yong Chen (Bioresource Technology, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Shimia fortis sp. nov., Isolated from Marine Sediment - Xiao-Yu Dong; Pei-Ran Lin; Xin-Yun Tan; Jia-Qi Li; Zong-Jun Du; Meng-Qi Ye (Current Microbiology, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

Integrating ecosystem service supply-demand dynamics into watershed management: A novel framework for quantifying water purification services - Lei Tan; Guishan Yang; Qing Zhu; Rongrong Wan; Jun Li; Hengpeng Li; Bing Li (Water Research, 2026)

Lopinavir/ritonavir induces hepatotoxicity in HepG2 cells through inhibition of the Nrf2 pathway, resulting in oxidative stress, endoplasmic reticulum stress, and cell cycle arrest - Wenhong Zhou; Dan Wang; Jundou Tu; Jun Li; Jiayu Xu; Wenjing Tan; Diwei Mo; Pengying Liang; Yinglin Guo; Ming Hu; Linhu Ye (Toxicology Letters, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Synergistic oxyanion engineering on RuO2 enables highly active and stable acidic water oxidation - Longquan Li; Binhua Zhou; Xuanzhi Liu; Feng Liu; Meihuan Liu; Yue Yu; Huanhuan Zhai; Pengfei Tan; Jun Pan (Chemical Engineering Journal, 2026)

Brevibacillus nigriterrae sp. nov., a Novel Denitrification Bacterium Isolated from Black Soil - Jun Xiao; Xin-Ting Yuan; Le-Bin Chen; Yu-Ting OuYang; Xin Huang; Jia-Hao Tan; Jun Liu; Shuang Wang; Jian-Yu Jiao; Wen-Jun Li (Current Microbiology, 2026)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

Influence of solid-state fermentation with lactic acid bacteria on the structure, physicochemical and adsorption properties of dietary fiber in rice bran - Dan Wang; Xiao-Tong Zhai; Na-Na Wu; Jun Li; Ming Zhao; Na Zhang; Bin Tan (Food Bioscience, 2025)

Associations between PM2.5 components, temperature, and semen quality: Insights from seminal plasma metabolome - Jun-feng Tan; Li-li Huang; Zhong-Hua Lu; Hang-Yu Xiang; Hong Yang; Hai-Xia Zhou; Tian-qing Meng; Cheng-liang Xiong; Yi-Xin Wang; Jie Zhang (Environmental Research, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Effect of Accelerators on Hydrothermal Anaerobic Digestion of Platanus Orientalis Linn Fallen Leaves - Hui Tan; Hongyu Huo; Jun Zhou; Mingjing Li; Jiahui Zhu; Lei Gong; Wenfeng Wang; Ping Yang (Water, Air, & Soil Pollution, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

TTI Medium Anisotropic Reverse Time Migration Imaging and Its Application in Oil and Gas Exploration in the Xihu Depression of the East China Sea - Shunli Gao; Peng Song; Yun Wei; Wenjun Wang; Jun Tan; Caixia Zhao; Shibo Mao; Jianghe Dong; Qingquan Li (Journal of Ocean University of China, 2025)

Gestational joint exposure to air pollutants and intrauterine skeletal development: Mediating effect of placental metabolome in a Chinese birth cohort - Zhong-Hua Lu; Chong Liu; Chen Tang; Jun-Feng Tan; Hao Chang; Yu-Jie Chen; Guang-Ming Li; Wen-Qing Lu; Yi-Xin Wang; Jie Zhang (Journal of Hazardous Materials, 2025)

Response of abundant and rare microbial taxa to three iron-carbon composite amendments in metal-contaminated agricultural soil - Ting Yang; Jiacan Li; Ying Yuan; Xin Zheng; Yifei Liu; Bing Zhang; Tan Chen; Jun Jin; Linlan Zhuang (Journal of Environmental Sciences, 2025)

Crystal-scale heterogeneity of Sn isotopes in Cassiterite: implications for reconstructing ore-forming processes in magmatic-hydrothermal systems - Liang Han; Guo-Guang Wang; Pei Ni; Jun-Yi Pan; Jia-Xin She; Wei Tan; Weiqiang Li (Geochimica et Cosmochimica Acta, 2025)

Laboratory characterization of VOC evaporative emissions from light-duty plug-in hybrid electric vehicles: Environmental impact comparison with conventional vehicles - Ling Li; Rui Yuan; Wei Hu; Hualong Xu; Pingjiang Lv; Qin Xu; Jun Wang; Xue Jiang; Jianxun Tan; Jianli Yin; Zhenliang Li; Dan Zhang (Environmental Pollution, 2025)

Optimized N-type Bi2Te2.4Se0.6 thermoelectric materials enabling homogeneous segmented device - Lidong Chen; Ruijie Li; Yongye Ding; Jingtao Xu; Liya Miao; Chuandong Zhou; Xiaojian Tan; Li Kong; Jiehua Wu; Guo-Qiang Liu; Jun Jiang (Chemical Engineering Journal, 2025)

Pulse Frequency and Water Velocity Determine Crossing Probability in Pulsed Direct-Current Fish Barriers - Wanshuang Yi; Lu Cai; Yun Tan; Bo Xu; Jun Li; Lianwei Liu; Lanlan Xu; David Johnson; Shihong Zhu; Guosheng Yang (Fishes, 2025)
Fish barrier technology by pulsed direct current has broad application potential to guide fish to suitable waters. The primary objective of this investigation was to study the effects of electric pulse frequency and water velocity on fish deterrence by pulsed direct current. The test fish were adults of two common carp species, Hypophthalmichthys nobilis (bighead carp, standard length 0.460–0.545 m) and Cyprinus carpio (Eurasian carp, standard length 0.292–0.335 m). Experiments were conducted in the 20 m swimming chamber of a 50 m flume, with a pulsed electric barrier produced by vertical electrodes located in the middle of the swimming chamber. The effectiveness of the electric barrier in deterring fish from swimming upstream past the electrodes was tested. The electric pulse generator produces a square wave pulse, with a voltage of 150 V and width of 2 ms. There were four electric pulse frequency treatments (4 Hz, 6 Hz, 8 Hz, 10 Hz), and two water velocity treatments (0.2 m/s, 0.6 m/s), with 10 replicates of each treatment. There were four primary findings. (1) Of the 160 fish tested, no fish was stunned and only 4 trembled (lost the ability to swim) for more than 2 s after encountering the electric barrier. (2) At a given water velocity, the crossing probability decreased as pulse frequency increased, and the decrease was largest when the frequency increased from 8 to 10 Hz. (3) At a given electric pulse frequency, the crossing probability was higher at the high water velocity, and barrier efficiency was more sensitive to velocity at higher pulse frequencies. (4) H. nobilis, a stronger swimmer, crossed more often than C. carpio. This study can provide ideas for the management of invasive species. However, the study was conducted under controlled laboratory conditions, and field experiments should be carried out before field applications.

Preclinical pharmacokinetic and toxicokinetic profiles of AY-1001 (IsoLiPro), a novel small molecule lithium-organic coordination compound - Yi Guo; Bingjie Zhang; Chuanbin Cai; Qinmin Tang; Zhifeng Lei; Jiang Chen; Xiaojiang Zheng; Shaowei Lei; Weidi Zhang; Dan Zi; Jun Tan; Song Li (Toxicology and Applied Pharmacology, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

A small block treatment method in three-dimensional block identification for rock block system mechanical analysis - Zheqi Tian; Jun Zheng; Ruichen Zhang; Qing Lü; Shengkui Tan; Junfeng Li (Computers and Geotechnics, 2025)

High-efficiency enrichment process of uranium from amidoxime-functionalized fibers after treated by alkaline elution system - Shen Zhang; Wencai Cheng; Congcong Ding; Ze Qiu; Junwen Tan; Xirui Lu; Jun Wen; Hao Li (Chemical Engineering Journal, 2025)

Hydroxylation of IrO2 via La doping enhances oxygen evolution reaction performance for PEM water electrolysis - Binhua Zhou; Xuanzhi Liu; Longquan Li; Meihuan Liu; Hanxiao Liao; Yue Yu; Feng Liu; Pengfei Tan; Jun Pan (Chemical Engineering Journal, 2025)

Molecular detection and phylogenetic analysis of lumpy skin disease virus in Yunnan Province, China from 2019 to 2023 - Jun Yao; Xue Li; Lei Tan; Lin Gao; Pei Zhu; Jiarui Xie; Rui Yan; Taoyin Yu; Fengyi Xia; Qiyun Chen; Bangquan Zeng; Jiaping Yang (Veterinary Research Communications, 2025)

Impact of plant litter decomposition on soil microbial diversity and ecosystem multifunctionality - Quanchao Zeng; Lianhao Zhou; Quan Zhou; Jun Li; Zhe Chen; Man Hu; Wenfeng Tan (Applied Soil Ecology, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Investigating the role of advanced catalysts and technologies in enhancing CO2 conversion via reverse water-gas shift reaction - Changxuan Zhang; Zhourong Xiao; Xining Guo; Xinyi Tan; Jianmin Gu; Junjie Li; Guozhu Li; Ji-Jun Zou; Desong Wang (Chemical Engineering Journal, 2025)

Enhancing lipid yield in freshwater microalgae through synergistic abiotic stressors for sustainable biodiesel production - Uganeeswary Suparmaniam; Cheng Yaw Li; Man Kee Lam; Nurul Tasnim Sahrin; Hemamalini Rawindran; Chin Seng Liew; Jun Wei Lim; Inn Shi Tan; Sie Yon Lau; Bridgid Lai Fui Chin (Biomass and Bioenergy, 2025)

Black carp OTUD1 negatively regulates antiviral innate immunity via deubiquitination and degradation of IRF3/7 - Shasha Tan; Yixin Chen; Jiaxin Wang; Zhan'ao Li; Jinyi Li; Hanbo Liu; Jiajie Yu; Ruimin Yue; Jun Xiao; Hui Wu; Jun Yan; Jun Zou; et al. (Fish & Shellfish Immunology, 2025)

Targeted TGF-βR2 Silencing in the Retrotrapezoid Nucleus Mitigates Respiratory Dysfunction and Cognitive Decline in a Mouse Model of Cerebral Amyloid Angiopathy with and without Stroke - Ahmad El Hamamy; Zahid Iqbal; Ngoc Mai Le; Arya Ranjan; YuXing Zhang; Hung Wen Lin; Chunfeng Tan; Destiny Sumani; Anthony Patrizz; Louise D. McCullough; Jun Li (Translational Stroke Research, 2025)

ZFYVE1 suppresses IRF3/7-mediated antiviral innate immunity in black carp - Zewen Yi; Jiaxin Wang; Shasha Tan; Zhan'ao Li; Xinyu Wang; Jiajie Yu; Ruimin Yue; Jun Xiao; Hui Wu; Hao Feng (Fish & Shellfish Immunology, 2025)

Association of organophosphate flame retardants exposure with liver function and the contrasting mediating roles of inflammatory and oxidative stress pathways - Yingyi Dai; Qin Li; Yongxian Li; Si Zhou; Xiaotong Li; Chongshan Guo; Jun Yuan; Lei Tan (Environmental Pollution, 2025)

Suppressive Ru oxidation and activated lattice oxygen in Mn doped RuO2 for efficient acidic oxygen evolution reaction - Yue Yu; Feng Liu; Xuanzhi Liu; Longquan Li; Binhua Zhou; Hanxiao Liao; Pengfei Tan; Jun Pan (Chemical Engineering Journal, 2025)

High-performance lithium storage anode: Polypyrrole-coated microrods BiSBr with conversion-alloying dual mechanism - Yonggen Tan; Sen Li; Zhiyuan Huang; Wanda Kang; Yingkai Hua; Xingchen Liu; Guiwen Luo; Xi Chen; Jun Feng (Chemical Engineering Journal, 2025)

Regulation of reactive oxygen species in peroxymonosulfate activation by metal–organic framework-derived materials - Bolun Yu; Jun Chen; Aoli Tan; Shuoyang Li; Quanzhang Liu; Bowen Liang; Xiaohang Zhang; Zuhong Lin; Haipu Li; Jingjing Yao (Chemical Engineering Journal, 2025)

A Method for Mining Spatial Co-location Patterns Based on Contextual Similarity Among Categories - Xusheng Zhou; Yongbin Tan; Zhonghai Yu; Xiaolong Li; Youneng Su; Jun Wu (Journal of Geovisualization and Spatial Analysis, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Copper oxide nanoparticles disrupt lysosomal function and promote foam cell formation in RAW264.7 macrophages - Yilin Luo; Kun Zhang; Lejiao Mao; Meiling Tan; Xiaomei Dong; Na Li; Yuexing Zhou; Chengzhi Chen; Zhen Zou; Jun Zhang (Toxicology, 2025)

Metformin-induced precise targeted inhibition of ischemic neuronal death by a programable endogenous ROS-responsive nanoprodrug - Xiaofeng Tan; Ying Li; Hao Jin; Yu Zhou; Wenjun Li; Yun Zhao; Jun Hai; Jinyao Li; Zhongxiong Fan; Lichao Yang (Chemical Engineering Journal, 2025)

A new sulphur-containing metabolite from a mangrove endophytic fungus Aspergillus sp. GXNU-MA - Furong Wu; Wenxiu Zhang; Xianglong Bo; Qin Feng; Meijing Tan; Shichao Ju; Zishuo Song; Jun Li; Xishan Huang (Natural Product Research, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

VvABF5 promotes ABA-mediated chlorophyll degradation by transcriptional activation of VvSGR during rachis browning of grape - Zhiqian Li; Dongfang Zou; Changjiang Nie; Xing Chen; Chang He; Xianbo Zheng; Bin Tan; Jun Cheng; Wei Wang; Pedro Martínez Gómez; Xia Ye; Jiancan Feng (Postharvest Biology and Technology, 2025)

Anchoring multi-mechanism coupled miniature redox reactors with photothermal foam gels for simultaneous photoreduction U(VI) and interfacial evaporation from wastewater - Jia-Liang Yang; De-Bin Ji; Heng-Yu Tan; Zhi-Qiang Qiao; Zhi-Da Li; Dan-Dan Yuan; Hong-Jun Wu (Journal of Cleaner Production, 2025)

PpSPL1 and PpSPL15 inhibit peach branching by increasing strigolactone synthesis - Wan Pei; Jie Zhang; Ruixian Shen; Hefang Xie; Yajia Zhang; Junjie Zhang; Xiaodong Lian; Haipeng Zhang; Nan Hou; Lei Wang; Xianbo Zheng; Jun Cheng; et al. (Planta, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Chronic intermittent hypoxia modulates energy metabolic pathways and improves hypoxia tolerance capacity in golden pompano, Trachinotus blochii - Geng Hui Fang; Xiao Li Zhou; Chun Li Ran; Chun Xiu Jin; Shao Yang Bu; Yue Chen; Yong Gong; Zeng Tan Hu; Fei Biao Song; Jian Luo; Jun Long Sun (Science of The Total Environment, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

DHMMF, a natural flavonoid, suppressed gastric cancer growth by inducing apoptosis and autophagy via up-regulation of MAPK/c-Jun and Atg3/LC3 signaling - Xiaonan Chen; Longyan Wang; Huiming Huang; Fei Wang; Yingying Tian; Xuejiao Wei; Peng Tan; Zhuguo Wang; Pengfei Tu; Zhongdong Hu; Jun Li (Food Bioscience, 2025)

High-efficiency flavonoid deglycosylation of whole cells with surface display of α-L-rhamnosidase in Escherichia coli - Cheng-Hai Yan; Ding Wang; Ruo-Xi Mei; Lu Tan; Yi-Jiang-Cheng Li; Richard Ansah Herman; Yan Xu; Lu-Chan Gong; Jun Wang (Food Bioscience, 2025)

Electricity transmission and its effects on resource misallocation and environmental consequences in China: An economic analysis - Ruipeng Tan; Jun Li; Feng Wang; Jing Yang (Energy Policy, 2025)

Uncertainty analysis and parameter optimization of a water yield ecosystem service model: A case study of the Qilian Mountains, China - Bei Wang; Gao-Feng Zhu; Jun-Tao Zhong; Chun-Feng Ma; Ling Zhang; Mei-Bao Tan; Xin Li (Science of The Total Environment, 2025)

Examining the effects of processing techniques on the quality of hawk tea through liquid chromatography–tandem mass spectrometry and two-dimensional gas chromatography–time-of-flight mass spectrometry - Gong Feng; Jiacheng Li; Jun Liu; Rong Tan (Food Chemistry, 2025)

Regulation of silanol nests in zeolite to form stable Td-Co(II) species for efficient propane dehydrogenation - Huihui Deng; Baozhen Li; Wenchun Zheng; Qin Sun; Mengjia Zhu; Jun Zuo; Yu Tang; Lizhi Wu; Li Tan (Chemical Engineering Journal, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

Occurrence, toxicity, and control of halogenated aliphatic and phenolic disinfection byproducts in the chlorinated and chloraminated desalinated water - Youwei Jiang; Shuang Zang; Yue Qiao; Yirang Tan; Hongfei Tao; Qiao Li; Yingjie Ma; Xianshi Wang; Jun Ma (Water Research, 2025)

The PHD transcription factor ThPHD5 regulates antioxidant enzyme activity to increase salt tolerance in Tamarix hispida - Yao-Shuo Tan; Jing-Hang Li; Pei-Long Wang; Dan-Ni Wang; Bai-Chao Liu; Sonethavy Phetmany; Yong-Xi Li; Qing-Jun Xie; Cai-Qiu Gao (Plant Science, 2025)

Sesquiterpenoids from the roots and rhizomes of Valeriana officinalis var. latifolia - Jia-Jin Liu; Min Tan; Li-Zhong Wang; Jun-Jie Hao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

ATG4B as a novel biomarker for abdominal aortic aneurysm: integrated evaluation through experimental and bioinformatics analyses - Jingjing Jing; Qiuyan Sun; Rongqi Zhang; Chao Yang; Jun Yang; Chunyan Ma; Tan Li (Molecular and Cellular Biochemistry, 2025)

Unveiling the critical roles of nascent MnO2 in accelerating permanganate carbocatalysis - Jun Wang; Simeng Bi; Li Wei; Yi Shen; Fanpeng Meng; Yang Zhang; Xiaoyao Tan (Journal of Hazardous Materials, 2024)

The CeO2 morphology modulates the density and catalytic performance of dual-active site for enhancing the palmitic acid conversion - Hui Xin; Xilei Chen; Cuncun Xiao; Jun Chao; Hualong Zhang; Jiwei Tan; Changwei Hu; Lan Wu; Dan Li (Fuel, 2024)

The Prophylactic Protection of Salmonella Typhimurium Infection by Lentilactobacillus buchneri GX0328-6 in Mice - Yan Shi; Hao Peng; Yuying Liao; Jun Li; Yangyan Yin; Hongyan Peng; Leping Wang; Yizhou Tan; Changting Li; Huili Bai; Chunxia Ma; Wenbao Tan; et al. (Probiotics and Antimicrobial Proteins, 2024)
Salmonellosis is a disease caused by non-typhoid Salmonella, and although some lactic acid bacteria strains have been shown previously to relieve Salmonellosis symptoms, little has been studied about the preventive mechanism of Lentilactobacillus buchneri ( L. buchneri ) against Salmonella infection in vivo. Therefore, the L. buchneri was fed to C57BL/6 mice for 10 days to build a protective system of mice to study its prevention and possible mechanisms. The results showed that L. buchneri GX0328-6 alleviated symptoms caused by Salmonella typhimurium infection among C57BL/6 mice, including low survival rate, weight loss, increase in immune organ index and hepatosplenomegaly, and modulated serum immunoglobulin levels and intrinsic immunity. Importantly, the L. buchneri GX0328-6 enhanced the mucosal barrier of the mouse jejunum by upregulating the expression of tight junction proteins such as ZO-1, occludins, and claudins-4 and improved absorptive capacity by increasing the length of mouse jejunal villus and the ratio of villus length to crypt depth and decreasing the crypt depth. L. buchneri GX0328-6 reduced the intestinal proliferation and invasion of Salmonella typhimurium by modulating the expression of antimicrobial peptides in the intestinal tract of mice, and reduced intestinal inflammation and systemic spread in mice by downregulating the expression of IL-6 and promoting the expression of IL-10. Furthermore, L. buchneri GX0328-6 increased the relative abundance of beneficial bacteria colonies and decreased the relative abundance of harmful bacteria in the cecum microflora by modulating the microflora in the cecum contents.

Retraction Note: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2024)

Effects of dietary vitamin D3 and carbohydrate levels on growth performance, carbohydrate metabolism, and intestinal health of yellow catfish (Pelteobagrus fulvidraco) - Li-Xiang Wu; Qing-Lin Li; Zhi Luo; Mette Sorensen; Xiao-Lei Wei; Hua-Jun Zhang; Xiao-Ying Tan (Aquaculture, 2024)

A novel cascade catalysis for one-pot enzymatically modified isoquercitrin (EMIQ) conversion from rutin and sucrose using rationally designed gradient temperature control - Yu-Fan Zhan; Zhuo-Hao Meng; Cheng-Hai Yan; Min Tan; Marriam Khurshid; Yi-Jiangcheng Li; Shao-Jun Zheng; Jun Wang (Food Chemistry, 2024)

Black carp RNF135 enhances RIG-I-mediated antiviral signaling by facilitating its oligomerization - Chushan Dai; Yujia Miao; Zhan'ao Li; Yumian Liu; Ji Liu; Xiaoyu Liu; Shasha Tan; Hui Wu; Jun Xiao; Jun Zou; Hao Feng (Fish & Shellfish Immunology, 2024)

Impact of COVID-19 on temporal trends and health risks of urinary metal concentrations among residents of Guangzhou, China - Jia Liao; Rende Huang; Xiangyu Jia; Jia He; Qin Li; Xiaotong Li; Jun Yuan; Lei Tan (Environmental Research, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

AgNPs/CNTs modified nonwoven fabric for PET-based flexible interdigitated electrodes in pressure sensor applications - Weili Zhao; Jun Natsuki; Vuong Dinh Trung; Haoyi Li; Jing Tan; Weimin Yang; Toshiaki Natsuki (Chemical Engineering Journal, 2024)

Highly efficient electrochemiluminescent properties of porphyrin-based metal-organic framework Zn-TCPP and its immunoassay application to the detection of ochratoxin A - Xiaolin Fan; Cheng Tan; Xiao Mei; Jun Ma; Kang Wu; Anping Deng; Xinjian Feng; Jianguo Li (Analytica Chimica Acta, 2024)

Longitudinal study and predictive modelling of urinary pesticide metabolite concentrations in residents of Guangzhou, China - Xiangyu Jia; Xiaotong Li; Fenfang Deng; Jia He; Qin Li; Chongshan Guo; Jun Yuan; Lei Tan (Chemosphere, 2024)

Corrigendum to “Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder” [Ocean Eng. 294 (15 February 2024), 116683] - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

Sludge-based biochar preparation: pyrolysis and co-pyrolysis methods, improvements, and environmental applications - Jun Cao; Yutong Jiang; Xiao Tan; Lei Li; Songshan Cao; Jiayao Dou; Runqi Chen; Xiaoyun Hu; Zhiheng Qiu; Ming Li; Ziyin Chen; Hualun Zhu (Fuel, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

The role of gut microbiota in MP/NP-induced toxicity - Yinping Pan; Haojie Zhang; Liancai Zhu; Jun Tan; Bochu Wang; Minghui Li (Environmental Pollution, 2024)

Ozone sensitivity regimes vary at different heights in the planetary boundary layer - Xin Li; Wenjie Wang; Suding Yang; Yafang Cheng; Limin Zeng; Xuena Yu; Sihua Lu; Ying Liu; Min Hu; Shaodong Xie; Xiaofeng Huang; Jun Zhou; et al. (Science of The Total Environment, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

Effects of Fe(III) on the formation and toxicity alteration of halonitromethanes, dichloroacetonitrile, and dichloroacetamide from polyethyleneimine during UV/chlorine disinfection - Tingting Huang; Lin Deng; Shui Wang; Chaoqun Tan; Jun Hu; Bingqing Zhu; Mengya Li; Lianghua Lu; Zhihua Yin; Bowen Fu (Water Research, 2024)

Bayesian analysis of physiologically based toxicokinetic (PBTK) modeling for pentachlorophenol exposure in pregnant women - Chunfeng Wu; Yajiao Tan; Xiaoyi Wei; Xun Li; Sifei Sun; Bing Lyu; Zhen Shen; Xiao Wei; Shuo Xiao; Yuanyuan Ruan; Jun Yu; Gengsheng He; et al. (Toxicology in Vitro, 2024)

Comparative study of organic removal by pre-adsorption oxidation and synchronous adsorption oxidation processes: Performance and mechanism - Bo Tan; Ge Gou; Yi Ren; Zhuoyao Fang; Chao Liu; Bo Lai; Naiwen Li; Jun Li (Journal of Hazardous Materials, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Innovative insights into dry fermented sausages flavor: Unraveling the impact of varied lactobacillus genera-driven fermentation - Sha-sha Zheng; Ying-ying Hu; Li-jun Tan; Liu Yang; Chun-yu Wang; Bao-cai Xu (Food Bioscience, 2024)

Enhanced functionalization of nonwoven fabric by spray coating AgNPs/CNTs solution prepared by a one-step method - Weili Zhao; Vuong Dinh Trung; Haoyi Li; Jun Natsuki; Jing Tan; Weimin Yang; Toshiaki Natsuki (Chemical Engineering Journal, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Overexpression of the grape β-galactosidase gene VvBGAL3 delays the softening and extends the shelf life of tomato fruits - Shanshan He; Hongli Wei; Zhirui Xue; Meng Li; Jiannan Xie; Jiakang Qian; Xing Chen; Zhiqian Li; Chang He; Bin Tan; Xianbo Zheng; Jun Cheng; et al. (Postharvest Biology and Technology, 2024)

A comprehensive review on steam reforming of liquid hydrocarbon fuels: Research advances and Prospects - Zhourong Xiao; Changxuan Zhang; Shuran Huang; Senlin Zhang; Xinyi Tan; Zhiyou Lian; Ji-Jun Zou; Xiangwen Zhang; Guozhu Li; Desong Wang (Fuel, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

A rapid and efficient Agrobacterium-mediated transient transformation system in grape berries - Jiannan Xie; Chang He; Zhiqian Li; Meng Li; Shanshan He; Jiakang Qian; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Jidong Li; Jiancan Feng; et al. (Protoplasma, 2024)

Combining canopy spectral reflectance and RGB images to estimate leaf chlorophyll content and grain yield in rice - Zhonglin Wang; Xianming Tan; Yangming Ma; Tao Liu; Limei He; Feng Yang; Chuanhai Shu; Leilei Li; Hao Fu; Biao Li; Yongjian Sun; Zhiyuan Yang; et al. (Computers and Electronics in Agriculture, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

Exposure to the environmental pollutant chlorpyrifos induces hepatic toxicity through activation of the JAK/STAT and MAPK pathways - Huiyang Fu; Yao Ge; Xiyuan Liu; Siwei Deng; Jun Li; Peng Tan; Ying Yang; Zhenlong Wu (Science of The Total Environment, 2024)

Driving factors for distribution and transformation of heavy metals speciation in a zinc smelting site - Jin He; Chuxuan Li; Xingyao Tan; Zhihong Peng; Haidong Li; Xinghua Luo; Lu Tang; Jing Wei; Chongjian Tang; Weichun Yang; Jun Jiang; Shengguo Xue (Journal of Hazardous Materials, 2024)

Design, synthesis, and evaluation of 2,2’-bipyridyl derivatives as bifunctional agents against Alzheimer’s disease - Ren-Xian Tan; Wei-Hao Li; Jia-Min Pang; Si-Min Zhong; Xin-Yi Huang; Jun-Ze Deng; Lu-Yi Zhou; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2024)

Design and synthesis of novel factor XIa Inhibitors with bicyclic isoquinoline and naphthalene fragments - Yi Zhang; Linjun Dai; Yi Tan; Yongpeng Yu; Junhao Xing; Feng Yang; Boquan Ren; Yan-Jun Xu; Qing Li (Medicinal Chemistry Research, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Influences of pretreatment methods on the mechanical and environmental behaviors of PG-GGBS-LM ternary stabilizer - Joseph Roland Essama Atenga; Yunzhi Tan; Yongfeng Deng; Jun Wu; Dongming Cai; Wenqi Li (Environmental Science and Pollution Research, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Overexpressing peach PpePAO1 gene improves the nutrient value of tomato and enhances resistance against Botrytis cinerea - Zhenguo Cui; Yabo Jiang; Yang Chen; Xin Cheng; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Zhiqian Li; Xianbo Zheng; Jiancan Feng; et al. (Postharvest Biology and Technology, 2024)

Cell-excreted proteins mediate the interactions of differently sized silica nanoparticles during cellular uptake - Bin Huang; Jia-Ming Li; Xiao-Mei Zang; Mei Wang; Wei Pan; Ke-Da Zhang; Huan He; Qiao-Guo Tan; Ai-Jun Miao (Journal of Hazardous Materials, 2024)

Black carp ATG16L1 negatively regulates STING-mediated antiviral innate immune response - Yuqing Peng; Xiaoyu Liu; Shasha Tan; Jinyi Li; Le Tang; Youjia Liu; Jun Xiao; Hui Wu; Hao Feng (Fish & Shellfish Immunology, 2024)

Sciscionella sediminilitoris sp. nov., a Marine Actinomycete Isolated from Cape Rochado, Malaysia, and the Emendations to the Description of the Genus Sciscionella - Wee Fei Aaron Teo; Kavimalar Devaraj; Muhammad Nuruddin Mohd Nor; Wen-Jun Li; Geok Yuan Annie Tan (Current Microbiology, 2024)

Tunable vortex bound states in multiband CsV3Sb5-derived kagome superconductors - Zihao Huang; Xianghe Han; Zhen Zhao; Jinjin Liu; Pengfei Li; Hengxin Tan; Zhiwei Wang; Yugui Yao; Haitao Yang; Binghai Yan; Kun Jiang; Jiangping Hu; et al. (Science Bulletin, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Phenol degradation by a combined hydrogenation and photocatalytic oxidation over the bifunctional Rh/WO3 catalyst - Lizhi Tan; Haozhen Feng; Linyu Li; Hong Lin; Jun Xiong (Journal of Environmental Chemical Engineering, 2024)

A comprehensive review on photo-thermal co-catalytic reduction of CO2 to value-added chemicals - Zhourong Xiao; Peng Li; Hui Zhang; Senlin Zhang; Xinyi Tan; Fei Ye; Jianmin Gu; Ji-jun Zou; Desong Wang (Fuel, 2024)

Polybrominated diphenyl ethers in dust, hair and urine: Exposure, excretion - Junjie Jiang; Tianwei Li; Erde Wang; Yan Zhang; Jiali Han; Linli Tan; Xiang Li; Yuhao Fan; Ye Wu; Qianhui Chen; Jun Jin (Chemosphere, 2024)

Aspongopus chinensis ach-miR-276a-3p induces breast cancer cell cycle arrest by targeting APPL2 to regulate the CDK2-Rb-E2F1 signaling pathway - Renlian Cai; Samiullah Khan; Xumei Chen; Haiyin Li; Jun Tan; Ying Tian; Shuai Zhao; Zhiyong Yin; Tongxian Liu; Daochao Jin; Jianjun Guo (Toxicology and Applied Pharmacology, 2024)

Valorization of coconut peat to develop a novel shape-stabilized phase change material for thermal energy storage - Pin Jin Ong; Si Hui Angela Goh; Yihao Leow; Suxi Wang; Pei Wang; Zibiao Li; Xuesong Yin; Beng Hoon Tan; Warintorn Thitsartarn; Jianwei Xu; Xian Jun Loh; Dan Kai; et al. (Journal of Cleaner Production, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Ultrasoft bioadhesive hydrogel as a versatile platform for the delivery of basic fibroblast growth factor to repair traumatic brain injury - Bixin Shen; Junhui Wang; Tao He; Shihao Chen; Xue Wang; Jun Chen; Ruiqing Shi; Jing Wang; Hao Wang; Wenting Huang; Chengkun Cao; Xianxi Tan; et al. (Chemical Engineering Journal, 2024)

Mammalian STE20-like kinase 1 inhibits synoviocytes activation in rheumatoid arthritis through mitochondrial dysfunction mediated by SIRT3/mTOR axis - Min Tan; Jing Mao; Jianxiong Zheng; Yu Meng; Jun Li; Jiayao Hao; Haili Shen (Inflammation Research, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Phosphorus species transformation and recovery in deep eutectic solvent-assisted hydrothermal carbonization of sewage sludge - Rui Dou; Fan Gao; Yi Tan; Huan-Ran Xiong; Zhi-Xiang Xu; Sameh M. Osman; Li-Jun Zheng; Rafael Luque (Sustainable Chemistry and Pharmacy, 2024)

Iridoids and other constituents from the leaves and stems of Valeriana officinalis var. latifolia - Jia-Jin Liu; Jun-Jie Hao; Min Tan; Cai-Cen Liao; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2024)

Experimental investigation on hydrodynamic interaction between tsunami waves and bridge girder - Shaolin Yang; Zhiqiang Tan; Wanli Yang; Jun Luo; Ning Wang; Jun Li; Riran Wang (Ocean Engineering, 2024)

Exfoliated MXene/poly-melamine-formaldehyde composite membranes for removal of heavy metals and organics from aqueous solutions - Tian-Qi Zhang; Shuang Hao; Jun-Kai Zhao; Zhi-Qian Jia; Hong-Wei Tan; Yu Yang; Li-An Hou (Journal of Hazardous Materials, 2024)

Hydrophobic, elastic Cyclodextrin-based aerogel with stable broadband sound absorption - Jia-Xin Wang; Haoran Xu; Jun-Feng Feng; Shu-Ting Fan; Min Tan; Li Ma; Bang-Jing Li; Sheng Zhang (Chemical Engineering Journal, 2024)

Fatigue tests of multiplanar concrete-filled steel tubular KK-joints with inner ring stiffeners - Kang Wang; Xu-Hong Zhou; Seiichiro Tsutsumi; Jun-Xin Wu; Yu-Hang Wang; Ji-Ke Tan; Bin Wang; Shan Gao; Yu Li (Ocean Engineering, 2024)

Iodate(V) activated ferrate(VI) for enhanced oxidation of micropollutants from water and sediment media - Yi Ren; Bo Tan; Chao Liu; Chenghan Ji; Bo Lai; Weiming Zhang; Jun Li (Chemical Engineering Journal, 2024)

Sediment depth-related variations of comammox Nitrospira: Evidence in the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (Science of The Total Environment, 2023)

Combining physical approaches with deep learning techniques for urban building energy modeling: A comprehensive review and future research prospects - Zheng Li; Jun Ma; Yi Tan; Cui Guo; Xiao Li (Building and Environment, 2023)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Physiological and biochemical changes in leaf abscission of Cyclocarya paliurus stem segments in vitro - Qiu-Ying Li; Shuang Wang; Gao-Yin Wu; Ya Tan; Ying-Ying Liu; Cong-Jun Yuan; Shuang-Gui Geng; Ying-Liang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Soy, soil and beyond - Wee Kee Tan; Jingling Zhu; Jun Li; Choon Nam Ong (Soil Ecology Letters, 2023)

Application of Data-Driven technology in nuclear Engineering: Prediction, classification and design optimization - Qiao Hong; Ma Jun; Wang Bo; Tan Sichao; Zhang Jiayi; Liang Biao; Li Tong; Tian Ruifeng (Annals of Nuclear Energy, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Anti-contactin-associated protein-like 2 antibody autoimmune encephalitis with rapidly progressive parkinsonism: a case report and literature review - Xiaohong Qin; Jieying Li; Yuanyuan Luo; Yunsen He; Xiaoqiang Xiao; Arui Tan; Jun Xiao (Acta Neurologica Belgica, 2023)

α-LA attenuates microcystin-LR-induced hepatocellular oxidative stress in mice through Nrf2-mediated antioxidant and detoxifying enzymes - Jun Bai; Chaoyun Chen; Yaochuan Sun; Shangchun Li; Renjiang He; Qingbi Zhang; Qian Sun; Yu Huang; Ailin Tan; Li Yuan; Yinxing Huang; Yuanyuan Lan; et al. (Toxicon, 2023)

Variation and characterization of prometryn in oysters (Crassostrea gigas) after seawater exposure - Xiaojie Sun; Lihong Xing; Jun Xing; Xuying Zheng; Jiamin Liu; Jixing Peng; Zhaoxin Li; Zhijun Tan; Lianzhu Wang (Science of The Total Environment, 2023)

Ecytonucleospora hepatopenaei n. gen. et comb. (Microsporidia: Enterocytozoonidae): A redescription of the Enterocytozoon hepatopenaei (Tourtip et al., 2009), a microsporidian infecting the widely cultivated shrimp Penaeus vannamei - Yuan Wang; Jie Chen; Ying Na; Xin-cang Li; Jun-fang Zhou; Wen-hong Fang; Hong-xin Tan (Journal of Invertebrate Pathology, 2023)

Vertical variation in prokaryotic community composition and co-occurrence patterns in sediments of the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ping Huang; Shengjun Wu (Environmental Research, 2023)

Construction logic of ocean city branding: Based on cultural brand and cultural memory - Fuqiang Tan; Jianfei Zhu; Yijun Zou; Jun Ye; Xi Li (Ocean & Coastal Management, 2023)

PpeERF115 regulates peach fruit ripening by increasing polyamine turnover through up-regulation of genes involved in polyamine synthesis and catabolism - Xin Cheng; Zhenguo Cui; Yabo Jiang; Yang Chen; Bin Tan; Jun Cheng; Langlang Zhang; Xia Ye; Xiaobei Wang; Haipeng Zhang; Xiaodong Lian; Jidong Li; et al. (Postharvest Biology and Technology, 2023)

Extraction kinetics of separating molybdenum(Ⅵ) over iron(Ⅲ) from high acid leach solutions with mixtures of P507 and N235 - Miaomiao Peng; Keyu Shen; Yangjing Tan; Zhiyi Hu; Chun Liu; Zhixiong Liu; Wenbin Yan; Jun Hua; Fei Li (Minerals Engineering, 2023)

Effect of clay fraction on the mechanical properties and microstructural characteristics of waste rock fine-based brick - Sheng Zhang; Yunzhi Tan; Yongfeng Deng; Huajun Ming; Hui Li; Jun Wu (Journal of Cleaner Production, 2023)

Impacts of land-use change on carbon dynamics in China's coastal wetlands - Li-Shan Tan; Zhen-Ming Ge; Shi-Hua Li; Ke Zhou; Derrick Y.F. Lai; Stijn Temmerman; Zhi-Jun Dai (Science of The Total Environment, 2023)

Loss of Atg5 in Sertoli cells enhances the susceptibility of cadmium-impaired testicular spermatogenesis in mice - Yong-Wei Xiong; Dai-Xin Li; Zheng-Jia Ling; Lu-Lu Tan; Yu-Feng Zhang; Jin Zhang; Hao Li; Wei Chang; Hua-Long Zhu; Jun Zhang; Lan Gao; De-Xiang Xu; et al. (Food and Chemical Toxicology, 2023)

Elucidating the role of T-cell exhaustion-related genes in colorectal cancer: a single-cell bioinformatics perspective - Wei Tu; Yan Tu; Chunhong Tan; Honghong Zhong; Sheng Xu; Jun Wang; Lv Huang; Ling Cheng; Haoguang Li (Functional & Integrative Genomics, 2023)

A dual-photoelectrode fuel cell-driven self-powered aptasensor based on the 1D/2D In2S3/MoS2@Fe-CNTs heterojunction for the ultrasensitive detection of Staphylococcus aureus - Yu Li; Jun Tan; Mengfei Wang; Qiaojuan Jia; Shuai Zhang; Minghua Wang; Zhihong Zhang (Analytica Chimica Acta, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Association of maternal pre-pregnancy dietary intake with adverse maternal and neonatal outcomes: A systematic review and meta-analysis of prospective studies - Yunfeng Cui; Minqi Liao; Aihua Xu; Gengdong Chen; Jun Liu; Xiaoxuan Yu; Shuna Li; Xingyao Ke; Sixian Tan; Zeyan Luo; Qian Wang; Yanhua Liu; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Using Protection Motivation Theory to examine information-seeking behaviors on climate change - Jun Li; Ping Qin; Yifei Quan; Jie-Sheng Tan-Soo (Global Environmental Change, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Integrated fixed-film activated sludge systems in continuous-flow and batch mode acclimated from low to high aniline concentrations: Performance, mechanism and metabolic pathways - Nan-ping Wu; Qian Zhang; Bin Tan; Meng Li; Bing Lin; Jing He; Jun-hao Su; Hao-nan Shen (Bioresource Technology, 2023)

Targeted passivation and optimized interfacial carrier dynamics improving the efficiency and stability of hole transport layer-free narrow-bandgap perovskite solar cells - Xueqing Chang; Jun-Xing Zhong; Guo Yang; Ying Tan; Li Gong; Xing Ni; Yujin Ji; Youyong Li; Guodong Zhang; Yifan Zheng; Yuchuan Shao; Jie Zhou; et al. (Science Bulletin, 2023)

The mechanism of Se(IV) multisystem resistance in Stenotrophomonas sp. EGS12 and its prospect in selenium-contaminated environment remediation - Hongshi Xiao; Jun Tan; Mengjia Li; Zhihui Yuan; Haiyan Zhou (Journal of Hazardous Materials, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

RETRACTED ARTICLE: MiR-125 family improves the radiosensitivity of head and neck squamous cell carcinoma - Qi-Wei Wang; Ya-Nan Sun; Li-Jun Tan; Jian-Nan Zhao; Xiao-Jie Zhou; Tian-Jiao Yu; Jiang-Tao Liu (Molecular Biology Reports, 2023)
Background MiRNAs can affect the radiosensitization of head and neck squamous cell carcinoma (HNSCC). We aimed to analyze the function of miR-125 family members in HNSCC using The Cancer Genome Atlas (TCGA) and determine their effect on radiation in laryngeal squamous cell cancer (LSCC). Methods First, we systematically analyzed the role of the miR-125 family in HNSCC using the TCGA database and found that miR-125a-5p is associated with radiotherapy. We then performed comprehensive enrichment analysis of miR-125a-5p and predicted target genes. Then, we performed transfection, cell proliferation assays, reverse transcription polymerase chain reaction, apoptosis assays, micronucleus tests, and western blotting on hep-2 cells selected with puromycin. Results MiR-125 family members exhibited significantly different expression in HNSCC. They were significantly associated with tumor–node–metastasis staging, clinical stages, and histological grades. Radiation therapy had a statistically effect on miR-125 family members, except miR-125a-3p. Moreover, miR-125a-5p was related to overall survival in LSCC. Thus, we predicted 110 target genes and seven hub genes of miR-125a-5p. The proliferation rate of cells transfected with lentivirus vector expressing miR-125a-5p was significantly reduced compared to the other groups. The radiation effect was enhanced in cells transfected with miR-125a-5p. The ratio of apoptotic cells transfected and exposed to X-rays (10 Gy) was distinctly higher than that of the Ad-control group. Western blotting analysis revealed that miR-125a-5p upregulated the apoptotic regulators P53 and rH2AX. Thus, miR-125a-5p may increase radiosensitivity in LSCC via upregulation of pro-apoptotic genes. Conclusions MiR-125 family members could be prognostic biomarkers of HNSCC and improve HNSCC sensitivity to radiotherapy by activating P53. Upregulating miR-125a-5p via lentivirus vectors may be a novel strategy to strengthen the effect of radiotherapy on LSCC.

Study on the influence of coal fire on the temporal and spatial distribution of CO2 and CH4 gas emissions - Zhuangzhuang Shao; Bo Tan; Tianze Li; Meiyan Guo; Ruili Hu; Yan Guo; Haiyan Wang; Jun Yan (Environmental Science and Pollution Research, 2023)

Development and characterization of 50 SNP markers in three watersheds populations of Xenocypris davidi - Chaoqun Su; Chenxi Tan; Liangjie Zhao; Xinliang Peng; Jun Liu; Haolong Li; Xusheng Guo (Conservation Genetics Resources, 2023)

PpIBH1-1 limits internode elongation of peach shoot in a dose-dependent manner - Mengmeng Zhang; Beibei Feng; Yun Chen; Mingxi Geng; Ming Li; Xianbo Zheng; Haipeng Zhang; Langlang Zhang; Bin Tan; Xia Ye; Wei Wang; Jidong Li; et al. (Plant Science, 2023)

Polysaccharides from Artocarpus heterophyllus Lam. (jackfruit) pulp alleviate obesity by modulating gut microbiota in high fat diet-induced rats - Shunjiang Zeng; Jun Cao; Chenxi Wei; Yuzi Chen; Qibing Liu; Chuan Li; Yanjun Zhang; Kexue Zhu; Gang Wu; Lehe Tan (Food Hydrocolloids, 2023)

Thiomicrorhabdus marina sp.nov., an obligate chemolithoautotroph isolated from tidal zone sediment, and genome insight into the genus Thiomicrorhabdus - Xin-Yun Tan; Xin-Jiang Liu; Zhao Li; Fan Yu; Hui Yang; Zong-Jun Du; Meng-Qi Ye (Frontiers in Marine Science, 2023)
The contribution of microbes to the marine sulfur cycle has received considerable attention in recent years. In this study, a new Gram-stain-negative, aerobic sulfur-oxidizing bacterium, designated strain 6S2-11 T , was isolated from tidal zone sediment of the coast of Weihai, China. Strain 6S2-11 T was an obligate chemolithoautotroph utilizing thiosulfate as the energy source. Physiological and biochemical experiments, phylogenetic analysis, and comparative genomic analysis were done with strain 6S2-11 T . According to genomic analysis, strain 6S2-11 T owned a complete thiosulfate oxidation pathway and an untypical nitrogen metabolism pathway. Its relatively small genome also has multiple environmental adaptation mechanisms. The DNA G+C content of strain 6S2-11 T was 44.1%. Strain 6S2-11 T was observed to grow at 20-37°C (optimum, 35°C), pH 6.0-9.5 (optimum, pH 7.5), and 0.5-5% (w/v) NaCl (optimum, 2.5%). The major cellular fatty acids (>10%) of strain 6S2-11 T were Summed Feature 8 (C 18:1 ω7c/C 18:1 ω6c), C 16:0 and Summed Feature 3 (C 16:1 ω7c/C 16:1 ω6c). The comparison of 16S rRNA gene sequences indicated that strain 6S2-11 T was most closely to Thiomicrorhabdus xiamenensis G2 T (96.8%). Based on the results of phylogenetic analysis, the strain 6S2-11 T is a novel specie of the genus Thiomicrorhabdus , for which name Thiomicrorhabdus marina sp.nov. is proposed with the type strain 6S2-11 T (=MCCC 1H00523 T =KCTC 82994 T ).

FeNi3 foam as cathode catalyst in electrocatalytic peroxydisulfate system for enhanced Hg0 removal from simulated flue gas - Qianqian Zhang; Anchao Zhang; Hao Li; Xinmin Zhang; Zhijun Sun; Yanyang Mei; Jun Xiang; Sheng Su; Zengqiang Tan; Hao Lu (Journal of Environmental Chemical Engineering, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

A double-edged sword: role of apoptosis repressor with caspase recruitment domain (ARC) in tumorigenesis and ischaemia/reperfusion (I/R) injury - Kun Liu; Dongfeng Lan; Chunyang Li; Songpo Liu; Xiaofang Dai; Tao Song; Xianyao Wang; Qinghong Kong; Zhixu He; Jun Tan; Jidong Zhang (Apoptosis, 2023)

Effect of feeding level on growth, digestive and metabolic enzymes and antioxidant capacity in juvenile Yangtze sturgeon (Acipenser dabryanus) - Bin He; Bo Zhou; Hang Xie; Zeng-Tan Hu; Bin Wang; Jun-Lin Zhang; Qing-Zhi Li; Feng-Qi Zhao; Xing Liu; Qian-Dong Li; Tao Yan (Aquaculture, 2023)

Target-free vision-based approach for modal identification of a simply-supported bridge - Dong Tan; Jun Li; Hong Hao; Zhenhua Nie (Engineering Structures, 2023)

Tomographic evidences for hydraulic fracturing induced seismicity in the Changning shale gas field, southern Sichuan Basin, China - Yuyang Tan; Jiawei Qian; Jun Hu; Haijiang Zhang; Huilin Xing; Junlun Li; Jian Xu; Wen Yang; Ning Gu; Siyu Miao (Earth and Planetary Science Letters, 2023)

MUSER and IPS telescopes for solar and space weather observations - Yihua Yan; Wei Wang; Linjie Chen; Fei Liu; Jin Fan; Zhijun Chen; Lihong Geng; Chengming Tan; Suli Ma; Sha Li; Cang Su; Jing Du; et al. (Advances in Space Research, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Understanding the change of land space utilization efficiency with different functions and its coupling coordination: A case study of Urban Agglomeration in the Middle Reaches of the Yangtze River, China - Bin Yang; Jun Yang; Li Tan; Jianying Xiao (Journal of Geographical Sciences, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Carbon isotope composition of land snail shells as a proxy for precipitation amount in the East Asian Monsoon region: A case study from Hainan Island - Haolin Tan; Rui Bao; Chenlong Li; Xuefen Sheng; Jun Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

Drought risk assessment in the coupled spatial–temporal dimension of the Sichuan Basin, China - Tan Huizhi; Lu Xiaoning; Yang Shiqi; Wang Yongqian; Li Feng; Liu Jinbao; Chen Jun; Huang Yue (Natural Hazards, 2022)

Time Domain Full Waveform Inversion Based on Gradient Preconditioning with an Angle-Dependent Weighting Factor - Dongming Xia; Peng Song; Xishuang Li; Jun Tan; Chuang Xie; Shaowen Wang; Kai Liu; Bo Zhao; Shibo Mao (Journal of Ocean University of China, 2022)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Investigating the environmental impacts of coal mining using remote sensing and in situ measurements in Ruqigou Coalfield, China - Varinder Saini; Jun Li; Yinan Yang; Jinsong Li; Baoming Wang; Jun Tan (Environmental Monitoring and Assessment, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Multiple indeterminate domain (IDD)–DELLA1 complexes participate in gibberellin feedback regulation in peach - Yajun Jiang; Jiajia Chen; Xianbo Zheng; Bin Tan; Xia Ye; Wei Wang; Langlang Zhang; Jidong Li; Zhiqian Li; Jun Cheng; Jiancan Feng (Plant Molecular Biology, 2022)

The Macrophage IL-23/IL-17A Pathway: A New Neuro-Immune Mechanism in Female Mechanical Pain - Zhi Tan; Zhen-Jia Lin; Long-Jun Wu; Li-Jun Zhou (Neuroscience Bulletin, 2022)

Superiority of Adipose-derived CD34 + Cells over Adipose-derived Stem Cells in Promoting Ischemic Tissue Survival - Yan-Jun Liu; Tian-Yu Zhang; Poh-Ching Tan; Pei-Qi Zhang; Yun Xie; Qing-Feng Li; Shuang-Bai Zhou (Stem Cell Reviews and Reports, 2022)

Yohimbine Directly Induces Cardiotoxicity on Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Yiqi Gong; Li Yang; Jun Tang; Jijian Zheng; Nevin Witman; Philipp Jakob; Yao Tan; Minglu Liu; Ying Chen; Huijing Wang; Wei Fu; Wei Wang (Cardiovascular Toxicology, 2022)

Integrative testing device for investigating the hydro-mechanical behavior of highly expansive clay - Yun-zhi Tan; Fan Peng; Hui Li; Hua-jun Ming; De-an Sun (Arabian Journal of Geosciences, 2022)

Identification of A-to-I RNA editing profiles and their clinical relevance in lung adenocarcinoma - Cheng Wang; Mingtao Huang; Congcong Chen; Yuancheng Li; Na Qin; Zijian Ma; Jingyi Fan; Linnan Gong; Hui Zeng; Liu Yang; Xianfeng Xu; Jun Zhou; et al. (Science China Life Sciences, 2022)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

Three new ester glycosides with cytotoxic activity from the seeds of Caesalpinia sappan - Min Wang; Juan Tan; Jun Chen; Tian Xie; Liang-Mo Lin; Li-Li Zhong; Xing-Jun Cai; Qiong-Shi Wu (Natural Product Research, 2021)

Baicalin attenuates adriamycin-induced nephrotic syndrome by regulating fibrosis procession and inflammatory reaction - Ning Tan; Chen-Xia Sun; Hui-Jun Zhu; De-Yu Li; Sheng-Guang Huang; Shou-Di He (Genes & Genomics, 2021)

Hydrogeochemical and isotopic characteristics of spring water in the Yarlung Zangbo River Basin, Qinghai-Tibet Plateau, Southwest China - Ying-zhi Li; Zong-jun Gao; Jiu-tan Liu; Min Wang; Cong Han (Journal of Mountain Science, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Effects of prenatal exposure to bisphenols on newborn leucocyte telomere length: a prospective birth cohort study in China - Jun Liang; Yantao Shao; Dongping Huang; Chunxiu Yang; Tao Liu; Xiaoyun Zeng; Chunling Li; Zhenghua Tang; Jennifer Tan Hui Juan; Yanye Song; Shun Liu; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2021)

The Association Between Insular Subdivisions Functional Connectivity and Suicide Attempt in Adolescents and Young Adults with Major Depressive Disorder - Lan Hu; Muni Xiao; Jun Cao; Zhaojun Tan; Mengyao Wang; Li Kuang (Brain Topography, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Polyamine oxidase (PAO)–mediated polyamine catabolism plays potential roles in peach (Prunus persica L.) fruit development and ripening - Wei Wang; Xianbo Zheng; Shihao Liu; Bin Tan; Jun Cheng; Xia Ye; Jidong Li; Jiancan Feng (Tree Genetics & Genomes, 2021)

Down-regulation of MANNANASE7 gene in Brassica napus L. enhances silique dehiscence-resistance - Yu-Long Li; Yan-Kun Yu; Ke-Ming Zhu; Li-Na Ding; Zheng Wang; Yan-Hua Yang; Jun Cao; Li-Zhang Xu; Yao-Ming Li; Xiao-Li Tan (Plant Cell Reports, 2021)

New developments in anti-biofilm intervention towards effective management of orthopedic device related infections (ODRI’s) - Ping Li; Zhenwu Gao; Zhenwei Tan; Jun Xiao; Li Wei; Yirui Chen (Biofouling, 2021)

Distinct Effects of Social Stress on Working Memory in Obsessive-Compulsive Disorder - Qianqian Li; Jun Yan; Jinmin Liao; Xiao Zhang; Lijun Liu; Xiaoyu Fu; Hao Yang Tan; Dai Zhang; Hao Yan (Neuroscience Bulletin, 2021)
Stress might exaggerate the compulsion and impair the working memory of patients with obsessive-compulsive disorder (OCD). This study evaluated the effect of stress on the cognitive neural processing of working memory in OCD and its clinical significance using a “number calculation working memory” task. Thirty-eight patients and 55 gender- and education-matched healthy controls were examined. Stress impaired the performance of the manipulation task in patients. Healthy controls showed less engagement of the medial prefrontal cortex and striatum during the task under stress versus less stress, which was absent in the patients with OCD. The diagnosis × stress interaction effect was significant in the right fusiform, supplementary motor area, precentral cortex and caudate. The failure of suppression of the medial prefrontal cortex and striatum and stress-related hyperactivation in the right fusiform, supplementary motor area, precentral cortex, and caudate might be an OCD-related psychopathological and neural response to stress.

A novel displacement prediction method using gated recurrent unit model with time series analysis in the Erdaohe landslide - Yong-gang Zhang; Jun Tang; Zheng-ying He; Junkun Tan; Chao Li (Natural Hazards, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Integrating multisource RS data and GIS techniques to assist the evaluation of resource-environment carrying capacity in karst mountainous area - Jun-wei Pu; Xiao-qing Zhao; Pei-pei Miao; Si-nan Li; Kun Tan; Qian Wang; Wei Tang (Journal of Mountain Science, 2020)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Albian–Cenomanian A-type granite-related Ag–Pb–Zn veins in the central Yidun Terrane, SW China: constraints from the Xiasai deposit - Yan-Jun Li; Jun-Hao Wei; Jun Tan; Le-Bing Fu; Huan Li; Kun-Jia Ke (Mineralium Deposita, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Aspergillolide, a new 12-membered macrolide from sea cucumber-derived fungus Aspergillus sp. S-3-75 - Jun-Jie Tan; Xiao-Yu Liu; Yang Yang; Feng-Hua Li; Chang-Heng Tan; Yi-Ming Li (Natural Product Research, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Clinical and biochemical indexes from 2019-nCoV infected patients linked to viral loads and lung injury - Yingxia Liu; Yang Yang; Cong Zhang; Fengming Huang; Fuxiang Wang; Jing Yuan; Zhaoqin Wang; Jinxiu Li; Jianming Li; Cheng Feng; Zheng Zhang; Lifei Wang; et al. (Science China Life Sciences, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Time-Domain Full Waveform Inversion Using the Gradient Preconditioning Based on Transmitted Wave Energy - Peng Song; Jun Tan; Zhaolun Liu; Xiaobo Zhang; Baohua Liu; Kaiben Yu; Jinshan Li; Dongming Xia; Chuang Xie (Journal of Ocean University of China, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Changes in area and number of nature reserves in China - Zhijun Ma; Ying Chen; David S. Melville; Jun Fan; Jianguo Liu; Jinwei Dong; Kun Tan; Xuefei Cheng; Richard A. Fuller; Xiangming Xiao; Bo Li (Conservation Biology, 2019)
Nature reserves (NR) are the cornerstone of biodiversity conservation. Over the past 60 years, the rapid expansion of NRs in China, one of the world's megadiverse countries, has played a critical role in slowing biodiversity loss. We examined the changes in the number and area of China's NRs from 1956 to 2014 and analyzed the effect of economic development on the expansion of China's NRs from 2005 to 2014 with linear models. Despite a continuing increase in the number of NRs, the total area of China's NRs decreased by 3% from 2007 to 2014. This loss resulted from downsizing and degazettement of existing NRs and a slowdown in the establishment of new ones. Nature reserves in regions with rapid economic development exhibited a greater decrease in area, suggesting that downsizing and degazettement of NRs are closely related to the intensifying competition between economic growth and conservation. For example, boundary adjustments to national NRs, the most strictly protected NRs, along the coast of China's Yellow Sea, a global biodiversity hotspot with a fast‐growing economy, resulted in the loss of one‐third of the total area. One of the most important ecosystems in these NRs, tidal wetlands, decreased by 27.8% because of boundary adjustments and by 25.2% because of land reclamation. Our results suggest conservation achievement, in terms of both area and quality, are declining at least in some regions in the Chinese NR estate. Although the designation of protected areas that are primarily managed for sustainable use has increased rapidly in recent years in China, we propose that NRs with biodiversity conservation as their main function should not be replaced or weakened.

Advances in plant GDSL lipases: from sequences to functional mechanisms - Li-Na Ding; Ming Li; Wei-Jie Wang; Jun Cao; Zheng Wang; Ke-Ming Zhu; Yan-Hua Yang; Yu-Long Li; Xiao-Li Tan (Acta Physiologiae Plantarum, 2019)

Characterization of a new bunyavirus and its derived small RNAs in the brown citrus aphid, Aphis citricidus - Wei Zhang; Tengfei Wu; Mengmeng Guo; Tengyu Chang; Li Yang; Yang Tan; Chao Ye; Jinzhi Niu; Jin-Jun Wang (Virus Genes, 2019)

Genome-wide identification of Ziziphus jujuba TCP transcription factors and their expression in response to infection with jujube witches’ broom phytoplasma - Peng Chen; Jidong Li; Xia Ye; Bin Tan; Xianbo Zheng; Jun Cheng; Wei Wang; Huiyu Wang; Liyuan Gu; Jiancan Feng (Acta Physiologiae Plantarum, 2019)

Network of microRNA-transcriptional factor-mRNA in cold response of turbot Scophthalmus maximus - Miaomiao Nie; Xungang Tan; Yunliang Lu; Zhihao Wu; Jun Li; Dongdong Xu; Peijun Zhang; Feng You (Fish Physiology and Biochemistry, 2019)

Spatial distribution characteristics and environmental significance of phytoliths in surface sediments of Qingshitan Lake in Southwest China - Rencheng Li; Jun Fan; Richard S. Vachula; Shuhui Tan; Xiang Qing (Journal of Paleolimnology, 2019)

The relative strength of different floral visitors driving floral evolution within a Primula secundiflora population - Yun Wu; Tao Zhong; Guang-Li Liu; Lu-Wei Tan; Qing-Jun Li (Evolutionary Ecology, 2018)

A prediction scheme of tropical cyclone frequency based on lasso and random forest - Jinkai Tan; Hexiang Liu; Mengya Li; Jun Wang (Theoretical and Applied Climatology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

A novel active learning approach for the classification of hyperspectral imagery using quasi-Newton multinomial logistic regression - Kun Tan; Xue Wang; Jishuai Zhu; Jun Hu; Jun Li (International Journal of Remote Sensing, 2018)

Combined adaptive multiple subtraction based on optimized event tracing and extended wiener filtering - Jun Tan; Peng Song; Jinshan Li; Lei Wang; Mengxuan Zhong; Xiaobo Zhang (Journal of Ocean University of China, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Numerical simulation of longitudinal settlement of shield tunnel in the coastal city Shanghai - Li Yuan; Zhen-Dong Cui; Jun Tan (Marine Georesources & Geotechnology, 2017)

GWAS analysis of QTL for enteric septicemia of catfish and their involved genes suggest evolutionary conservation of a molecular mechanism of disease resistance - Tao Zhou; Shikai Liu; Xin Geng; Yulin Jin; Chen Jiang; Lisui Bao; Jun Yao; Yu Zhang; Jiaren Zhang; Luyang Sun; Xiaozhu Wang; Ning Li; et al. (Molecular Genetics and Genomics, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

The PI3K/Akt/mTOR pathway regulates the replicative senescence of human VSMCs - Pan Tan; Yan-Jiao Wang; Shuang Li; Yi Wang; Je-Yu He; Yi-Yin Chen; Hui-Qian Deng; Wu Huang; Jun-Kun Zhan; You-Shuo Liu (Molecular and Cellular Biochemistry, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Overexpression of sugarcane gene SoSnRK2.1 confers drought tolerance in transgenic tobacco - Thi-Thu Phan; Bo Sun; Jun-Qi Niu; Qin-Liang Tan; Jian Li; Li-Tao Yang; Yang-Rui Li (Plant Cell Reports, 2016)

Study on the Long-term Settlement of Subway Tunnel in Soft Soil Area - Jun Tan; Zhen-Dong Cui; Li Yuan (Marine Georesources & Geotechnology, 2016)

Salusin β Within the Nucleus Tractus Solitarii Suppresses Blood Pressure Via Inhibiting the Activities of Presympathetic Neurons in the Rostral Ventrolateral Medulla in Spontaneously Hypertensive Rats - Hong-Bao Li; Yan Lu; Jin-Jun Liu; Yu-Wang Miao; Tian-Zhen Zheng; Qing Su; Jie Qi; Hong Tan; Zu-Yi Yuan; Guo-Qing Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Isolation and identification of polyphenols from Marsilea quadrifolia with antioxidant properties in vitro and in vivo - Yuan Zhang; Hai-Yan Tian; Ya-Fang Tan; Yuk-Lau Wong; Hoi Yan Wu; Jun-Feng Jia; Guo-En Wang; Jing-Jing Gao; Yi-Fang Li; Hiroshi Kurihara; Pang-Chui Shaw; Ren-Wang Jiang (Natural Product Research, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Association study of protamine 2 (PRM2) gene polymorphism with male infertility in Chinese Han population - Xuemei Yang; Fang Liu; Jun Li; Yaman Song; Yuzhe Tan (Genes & Genomics, 2016)

Tissue-specific expression, developmentally and spatially regulated alternative splicing, and protein subcellular localization of OsLpa1 in rice - Hai-ping Lu; Wei-qin Pang; Wen-xu Li; Yuan-yuan Tan; Qing Wang; Hai-jun Zhao; Qing-yao Shu (Journal of Zhejiang University-SCIENCE B, 2016)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Selection of reference genes for quantitative real-time PCR normalization in creeping bentgrass involved in four abiotic stresses - Yu Chen; Baoyun Hu; Zhiqun Tan; Jun Liu; Zhimin Yang; Zhihua Li; Bingru Huang (Plant Cell Reports, 2015)

Enhanced production of poly-3-hydroxybutyrate by Escherichia coli over-expressing multiple copies of NAD kinase integrated in the host genome - Jie Zhang; Xue Gao; Peng-Hui Hong; Zheng-Jun Li; Tian-Wei Tan (Biotechnology Letters, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Mapping of quantitative trait loci for cold tolerance at the early seedling stage in landrace rice Xiang 743 - Wenqiang Liu; Tingting Lu; Yongchao Li; Xiaowu Pan; Yonghong Duan; Jun Min; Xiqin Fu; Xinnian Sheng; Junzhi Xiao; Sanxiong Liu; Jiang Tan; Yi Yao; et al. (Euphytica, 2015)

Fluorometric Titration Assay of Affinity of Tight-Binding Nonfluorescent Inhibitor of Glutathione S-transferase - Bangtian Xu; Deng Tan; Xiaolan Yang; Xiaolei Hu; Yanling Xie; Jialin Qin; Chunyan Chen; Chenxiong He; Yuanli Li; Jun Pu; Fei Liao (Journal of Fluorescence, 2015)

Production of low phytic acid rice by hairpin RNA- and artificial microRNA-mediated silencing of OsMIK in seeds - Wen-Xu Li; Jian-Zhong Huang; Hai-Jun Zhao; Yuan-Yuan Tan; Hai-Rui Cui; Yves Poirier; Qing-Yao Shu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Scoring the collective effects of SNPs: association of minor alleles with complex traits in model organisms - DeJian Yuan; ZuoBin Zhu; XiaoHua Tan; Jie Liang; Chen Zeng; JieGen Zhang; Jun Chen; Long Ma; Ayca Dogan; Gudrun Brockmann; Oliver Goldmann; Eva Medina; et al. (Science China Life Sciences, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Sensitivity analysis of the hydrological response of the Gaping River basin to radar-raingauge quantitative precipitation estimates - Tsung-yi Pan; Meng-ying Li; Yong-jun Lin; Tsang-jung Chang; Jihn-sung Lai; Yih-chi Tan (Hydrological Sciences Journal, 2014)

Activation of BKCa Channels Mediates Hippocampal Neuronal Death After Reoxygenation and Reperfusion - Ming Chen; Hong-Yu Sun; Ping Hu; Chun-Fei Wang; Bo-Xing Li; Shu-Ji Li; Jian-Jun Li; Hui-Ying Tan; Tian-Ming Gao (Molecular Neurobiology, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

A two-tube multiplex real-time RT-PCR assay for the detection of four hemorrhagic fever viruses: severe fever with thrombocytopenia syndrome virus, Hantaan virus, Seoul virus, and dengue virus - Zhifeng Li; Xian Qi; Minghao Zhou; Changjun Bao; Jianli Hu; Bin Wu; Shenjiao Wang; Zhongmin Tan; Jianguang Fu; Jun Shan; Yefei Zhu; Fenyang Tang (Archives of Virology, 2013)

Effects of Vinasse and Press Mud Application on the Biological Properties of Soils and Productivity of Sugarcane - Shang-Dong Yang; Jun-Xian Liu; Jun Wu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2013)

Binding properties of Ru(II) polypyridyl complexes with poly(U)·poly(A)*poly(U) triplex: the ancillary ligand effect on third-strand stabilization - Li-Feng Tan; Ling-Jun Xie; Xiao-Nan Sun (JBIC Journal of Biological Inorganic Chemistry, 2013)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Whole-body vibration and resistance exercise prevent long-term hindlimb unloading-induced bone loss: independent and interactive effects - Zhili Li; Cheng Tan; Yonghua Wu; Ye Ding; Huijuan Wang; Wenjuan Chen; Yu Zhu; Honglei Ma; Honghui Yang; Wenbin Liang; Shizhong Jiang; Desheng Wang; et al. (European Journal of Applied Physiology, 2012)

Origin of the Maoduan Pb–Zn–Mo deposit, eastern Cathaysia Block, China: geological, geochronological, geochemical, and Sr–Nd–Pb–S isotopic constraints - Yan-Jun Li; Jun-Hao Wei; Hua-Yong Chen; Jun Tan; Le-Bing Fu; Gang Wu (Mineralium Deposita, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Characteristics and evolution of the PUF gene family in Bombyx mori and 27 other species - Chun-Dong Zhang; Min-Hui Pan; Juan Tan; Fang-Fang Li; Jun Zhang; Ting-Ting Wang; Cheng Lu (Molecular Biology Reports, 2012)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

The Distribution and Cooperation of Antioxidant (Iso)enzymes and Antioxidants in Different Subcellular Compartments in Maize Leaves during Water Stress - Mingpu Tan; Jun Lu; Aying Zhang; Bing Hu; Xuewei Zhu; Wenbo Li (Journal of Plant Growth Regulation, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Geochronologies of the Huaixi copper-gold deposit and the Caomen alkaline granite, SE China: implications for tectonic evolution - Yanjun Li; Junhao Wei; Jun Tan; Chunliang Yao; Lina Peng; Guangling Xiao; Yunfei Yan; Zefu Ye (International Geology Review, 2011)

High-mobility group box 1 exacerbates concanavalin A-induced hepatic injury in mice - Quan Gong; Hui Zhang; Jun-hua Li; Li-hua Duan; Shan Zhong; Xiao-ling Kong; Fang Zheng; Zheng Tan; Ping Xiong; Gang Chen; Min Fang; Fei-li Gong (Journal of Molecular Medicine, 2010)

Total and speciated arsenic levels in rice from China - Feng Liang; Yulan Li; Guilin Zhang; Mingguang Tan; Jun Lin; Wei Liu; Yan Li; Wenwei Lu (Food Additives & Contaminants: Part A, 2010)

Field studies of the effectiveness of dynamic compaction in coastal reclamation areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He; Ke Tan (Bulletin of Engineering Geology and the Environment, 2010)

Two new N -oxide Lycopodium alkaloids from Huperzia serrata - Heng-Bin Wang; Chang-Heng Tan; Jun-Jie Tan; Shi-Jin Qu; Yi-Lei Chen; Yi-Ming Li; Shan-Hao Jiang; Da-Yuan Zhu (Natural Product Research, 2009)

Development and characterization of eight polymorphic microsatellites for Rhododendron simsii Planch (Ericaceae) - Xin-Xin Tan; Yong Li; Xue-Jun Ge (Conservation Genetics, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Cloning and Characterization of Two Novel Crystal Protein Genes, cry54Aa1 and cry30Fa1, from Bacillus thuringiensis Strain BtMC28 - Furong Tan; Jun Zhu; Jie Tang; Xueming Tang; Shiquan Wang; Aiping Zheng; Ping Li (Current Microbiology, 2009)

Molecular cloning and characterization of a novel transcript variant of Mtsarg1 gene - Li Li; Gang Liu; Jun-Jiang Fu; Lu-Yun Li; Xiao-Jun Tan; Sheng Yang; Guang-Xiu Lu (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Stock enhancement of the edible jellyfish (Rhopilema esculentum Kishinouye) in Liaodong Bay, China: a review - Jing Dong; Lian-xin Jiang; Ke-fei Tan; Hai-ying Liu; Jennifer E. Purcell; Pei-jun Li; Chang-chen Ye (Hydrobiologia, 2009)

Sodium butyrate-induced upregulation of p18 INK4C gene affects K562 cell G0/G1 arrest and differentiation - Lin Li; Guoping Zhang; Ye Zhang; Jiang Tan; Hui Huang; Baiqu Huang; Jun Lu (Molecular and Cellular Biochemistry, 2008)

Values of endoscopic ultrasonography for diagnosis and treatment of duodenal protruding lesions - Guo-qiang Xu; Yi-qun Wu; Li-jun Wang; Hong-tan Chen (Journal of Zhejiang University-SCIENCE B, 2008)

Protective effects of daviditin A against endothelial damage induced by lysophosphatidylcholine - De-Jian Jiang; Jun-Lin Jiang; Gui-Shan Tan; Yan-Hua Du; Kang-Ping Xu; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Identification of quantitative trait loci (QTLs) for the characters of vascular bundles in peduncle related to indica-japonica differentiation in rice (Oryza sativa L.) - Zhi-Hong Zhang; Ping Li; Ling-Xia Wang; Chang-Jun Tan; Zhong-Li Hu; Ying-Guo Zhu; Li-Huang Zhu (Euphytica, 2002)

Activation of Signal Transduction Kinases by Tamoxifen - Jauh-Lin Duh; Rong Yu; Jie-Jun Jiao; George A. Matwyshyn; Wei Li; Tse-Hua Tan; A.-N. Tony Kong (Pharmaceutical Research, 1997)